2013
DOI: 10.1053/j.gastro.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Much of the Genetic Risk of Colorectal Cancer Is Likely to Be Mediated Through Susceptibility to Adenomas

Abstract: Several single nucleotide polymorphisms (SNPs) have been associated with colorectal cancer (CRC) susceptibility. Most CRCs arise from adenomas, and SNPs might therefore affect predisposition to CRC by increasing adenoma risk. We found that 8 of 18 known CRC-associated SNPs (rs10936599, rs6983267, rs10795668, rs3802842, rs4444235, rs1957636, rs4939827, and rs961253) were over-represented in CRC-free patients with adenomas, compared with controls. Ten other CRC-associated SNPs (rs6691170, rs6687758, rs16892766, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
8
22
0
Order By: Relevance
“…The association between SNP rs3802842 and CRC has been replicated in at least seven previous studies, with consistent positive associations [17]. Also, SNP rs6983267 has been replicated in at least 14 previous studies in Western populations [18]. Both SNPs have been previously reported in Asian populations but only SNP rs6983267 was found to be associated with rectal cancer in the present study.…”
Section: Genetic Factorssupporting
confidence: 85%
“…The association between SNP rs3802842 and CRC has been replicated in at least seven previous studies, with consistent positive associations [17]. Also, SNP rs6983267 has been replicated in at least 14 previous studies in Western populations [18]. Both SNPs have been previously reported in Asian populations but only SNP rs6983267 was found to be associated with rectal cancer in the present study.…”
Section: Genetic Factorssupporting
confidence: 85%
“…A variant in chromosome 8q24 initially described by admixture mapping for prostate cancer in African Americans also showed a positive association with colorectal cancer risk 30 and, recently, a case-control study reported an association of one 8q24 loci variant (rs380284) and adenoma risk in Caucasians. 39 In conclusion, we report for the first time that African ancestry (or variants linked to it) contributes to the susceptibility of colorectal cancer in admixed Latin American population. Our results are promising as they may help get insights of colorectal carcinogenesis and even more to find biomarkers useful to stratify colorectal cancer risk in the Latino populations, where colorectal mortality rates are increasing, although not high enough to recommend mass screening programs.…”
Section: Discussionmentioning
confidence: 65%
“…The positive association of African genetic ancestry with adenoma and colorectal cancer is consistent with a recent publication reporting that colorectal cancer risk is likely to be mediated through genetic susceptibility to adenomas. 39 Early detection of adenomas is a key issue in colorectal cancer control. Newly published evidence supports that detecting adenomas and removing them not only decreases the incidence but also the mortality of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these results reflect different variant alleles in the populations studied, given that the minor allele frequency was different. The rs4939827 SNP likely influences cancer via inhibition of SMAD7 [28,29] , a component of the transforming growth factor-β signalling pathway that regulates growth and apoptosis and plays an important role in cancer initiation and progression [30][31][32][33] . Despite the adequate statistical power of the current study, some limitations should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the association between genetic polymorphism and clinicopathologic type (adenocarcinoma or squamous cell carcinoma) was not evaluated. This could be an important factor, as rs4444235 and rs4939827 were shown to be over-represented in CRC-free patients with adenomas [32,33] .In conclusion, this association study investigated 31 SNPs identified from CRC GWAS as genetic susceptibility factors for esophageal cancer in a Chinese population. The replication of genetic associations from CRC to esophageal cancer highlights the utility of case-control studies to confirm novel associations characterized in large GWAS of digestive system diseases.…”
mentioning
confidence: 92%